Child labor and psychosocial wellbeing: Findings from India. (8th February 2021) - Feeny, Simon; Posso, Alberto; Skali, Ahmed; Jyotishi, Amalendu; Nath, Shyam; Viswanathan, P. K.
Abstract: Mental health is a neglected health issue in developing countries. We test if mental health issues are particularly likely to occur among some of the most vulnerable children in developing countries: those that work. Despite falling in recent decades, child labor still engages 168 million children across the world. While the negative impacts of child labor on physical health are well documented, the effect of child labor on a child's psychosocial wellbeing has been neglected. We investigate this issue with a new dataset of 947 children aged 12–18 years from 750 households in 20 villages across five districts of Tamil Nadu, India. Our purpose‐built survey allows for a holistic approach to the analysis of child wellbeing by accounting for levels of happiness, hope, emotional wellbeing, self‐efficacy, fear and stress. We use a variety of econometric approaches, some of which utilize household‐level fixed effects and account for differences between working and nonworking siblings. We document a robust, large and negative association between child labor and most measures of psychosocial wellbeing. The results are robust to a battery of exercises, including tests for selection on unobservables, randomization inference, instrumental variable techniques, and falsification exercises.